ФОРМУВАННЯ ІНФОРМАЦІЙНОЇ СИСТЕМИ ОРГАНІЗАЦІЇ В УМОВАХ ЦИФРОВОЇ ЕКОНОМІКИ (International Journal of Innovative Technologies in Economy, 2020)
The article reveals the role and importance of information, which is a dominant resource, acquires comprehensive significance for the life of society in a digital economy, determining its political, socio-economic and cultural development. In any organization, the aggregation of data into a single digital information space is important for the management system, which creates such an information infrastructure of the organization (IIO) that allows solving the tasks and is a kind of management loop through the prism of technological innovations. Therefore, the author has developed and proposed a model of the organization’s information infrastructure architecture, which contributes to the constant updating of innovations, methods and approaches to the information environment in the digital economy. The information management infrastructure of organizations is becoming a priority management object, requires consideration of its properties and specifics, due to the processes of digital modernization of the economy. The organization’s information infrastructure is a comprehensive system that covers information, personnel, a set of applied, technological and technical solutions to provide information support for the organization’s work in accordance with the rules and concept, mission and strategy of the organization, its business model and management approaches.